STUDENTS PERCEPTION OF TEACHER’S INVOLVEMENT IN ACADEMIC DISHONESTY - Ikiroma, Blessing; Anyanwu, Jerome (Advances in Social Sciences Research Journal, 2017)
This study examines the perception of senior secondary school students in Rivers State on the extent of teacher’s involvement in academic dishonesty. Subjects were 1,000 senior secondary school students in Rivers State drawn via multi-stage sampling technique. Data for the study were obtained through a questionnaire on a simple yes or no format which has a reliability coefficient of 0.87. Three research questions guided the study and frequency counts which were converted to simple percentages were deployed as statistical tools. The study revealed that a greater percentage of the students view their teachers as being involved very often in dishonest practices academically. The study also showed that inflation of continuous assessment/examination scores tops the lists in the views of the students’ as one of the ways that teachers contribute to academic dishonesty. This is followed with conspiracy of teachers with both students and security officials during examination, exchange of answers for money, and teachers impersonating students in that order. Based on these findings it was recommended among others, that teachers should spend more time in preparing students for examinations. If they do it, is likely that teachers would not be intimidated by parents to do what they would not naturally want to do. Key words: Secondary school students, Teachers, Academic Dishonesty, Rivers State